A Biochemical and Morphological Comparison of the Role of L-Arginine on the High Saturated and Unsaturated Fat Diet Induced Changes on Adrenocortical Cells of Albino Rats (Medical Forum Monthly, 2024)
Objective: Fatty diet produces both biochemical and histological changes in the adrenal cortex of albino rats. Present study objectives were to see if L-Arginine ameliorates the affects produced by both saturated and unsaturated fat equally.Study Design: A prospective experimental studyPlace and Duration of Study: This study was conducted at the Department of Anatomy, BMSI, JPMC, Karachi from August to October 2008.Materials and Methods: A total of 50 Albino rats weighing 200-240gms, aged 190days were divided into 5 groups. Group A received standard laboratory diet .Group B received 20% saturated added fat as unsalted butter in diet .Group C received 20% unsaturated added fat as corn oil in diet .Group D received saturated fat with L-Arginine 300mg /kg body weight /day orally. Group E received unsaturated fat along with L-Arginine 300mg/kg body weight/day orally. After 8 weeks study period, animals were weighed and sacrificed and blood was drawn for hormonal assays. Adrenal glands were removed and fixed in buffered neutral formalin. They were then sectioned with cryostat in 10µm sections and stained with Oil red O to visualize fat in cells.Results: Highly significant decrease observed in both ACTH and Corticosterone levels in Group D and E when compared to B and C respectively, but insignificant difference was found between D&E. Oil red O stained sections showed less densely packed fat globules in group D and E compared to B and C respectively. The results when compared between D and E were not significant.Conclusion: L-Arginine lowers down the level of stress hormones in body and amount of fat in cortical cells in both groups receiving saturated and unsaturated fat diet with L-Arginine but their comparison didn’t show significant difference statistically.